"Verticalised" cases before the European Court of Human Rights unravelled: An analysis of their characteristics and the Court's approach to them. Issue 4 (December 2020) - Loven, Claire
Based on Article 34 European Convention on Human Rights, individual applications must be directed against one of the Convention States. Originally 'horizontal' cases therefore must be 'verticalised' in order to be admissible. This means that a private actor who had first brought a procedure against another private actor before the domestic courts, must complain about State (in)action in his application to the European Court of Human Rights. Recently, some scholars and judges have raised procedural issues that may arise in these cases, but generally, these 'verticalised' cases have remained underexplored. To unravel verticalised cases before the ECtHR and to better understand procedural issues that may arise from them, this article provides a deeper understanding of the origins of verticalised cases and the Court's approach to them. It is explained that verticalised cases before the ECtHR can be very different in nature. These differences are rooted in the different types of horizontal conflicts that may arise on the domestic level, the different relations between private actors they may concern, and the different Convention rights that may be at stake. The wide variety of verticalized cases is also reflected in the Court's approach to them, as is the second main topic that the present article explores.